A Report of Two Cases: Post Flood Autopsy Findings in Urban Patients with An Unusual Presentation of Leptospirosis with Hemorrhagic Pneumonia in Government Medical College, Surat - Mandakini M Patel; Bhavna Gamit; R D Patel; Rahul Modi (Medsci Publications, 2011)
South Gujarat is endemic zone for leptospirosis in paddy workers but recently we have post flood plenty of urban patients who were presented with high grade fever, dyspnea & haemoptysis with rapid deterioration. Clinicians were suspecting an outbreak of Hantavirus or leptospirosis. Both our patients were serologically negative for leptospirosis ante mortem, but alveolar hemorrhage & raised urea was the only finding. Both our patient rapidly deteriorated. We performed autopsy & took post mortem samples for serologically & HP Examination of tissue. Serological finding showed one patient positive for PCR and second was positive for Leptocheck and IgM ELISA. On HP examination we observed massive intra-alveolar hemorrhage, interstitial nephritis, vasculitis in spleen and kidney, myocarditis & hemorrhage in various organs like heart, suprarenal gland, and subarachnoid space in both our patient. Levaditi's stain was also performed but results were not conclusive. IHC for kidney tissue was not possible due to lack of facility. Extensive hemorrhage in lung was the cause of death in both patients. Follow up autopsy studies of 30 patients were showing same histopathological findings.